Use of an Immunoglobulin G Avidity Test To Discriminate between Primary and Secondary Dengue Virus Infections - de Souza, Vanda Akico Ueda Fick (American Society for Microbiology, 2004)
An enzyme-linked immunosorbent assay-based immunoglobulin G (IgG) antibody avidity test was evaluated by using sera from 57 patients with acute dengue infection. Overall, 55 of 57 patients were correctly classified (27 of 27 with primary dengue and 28 of 30 with secondary dengue). We conclude that the IgG avidity test can be useful for differentiating between acute, primary, and secondary dengue infections.